The Effect Of Trust, Service Quality And Price On Customer Loyalty With Customer Satisfaction As An Intervening Variable At Jne Tanjung Pinang Branch - Wilia Octadina; Bambang Satriawan; Muammar Khaddafi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the direct and indirect effect of trust, service quality, price on customer loyalty through customer satisfaction at JNE Tanjung Pinang Branch. This type of research uses quantitative research methods with primary and secondary data sources. This research was conducted at JNE Tanjung Pinang Branch, Tanjung Pinang, Riau Islands. This research started from March 2023 to August 2023. Based on the results of JNE transaction data for Tanjungpinang City, the population taken is consumers from the corporate and social commerce types who trust the delivery of goods/files from companies or agencies with JNE. The population is 146 from both corporate and social commerce types who have collaborated with JNE Tanjung Pinang. In this study, data collection was carried out using the census method in which the entire population was taken as a sample. By using the census method, this study aims to obtain accurate and representative data from the entire existing population. This step will make it easier for researchers to analyze and describe the characteristics and events that occur in the population, Based on the provisions, the number of samples that meet the criteria from JNE users in the corporate and social community categories is 118 respondents. This research uses Smart-Pls as a data processing tool. The results of the study show that all variables have a direct and indirect effect on variables Z and Y.